Product differentiation in video games: A closer look at Fortnite's success - Karl-Heinz Moritz; Timo Schöber; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2020)
Fortnite is the most successful video game in terms of revenues generated. Since it belongs to the 'free-to-play games', the company has to optimize the in-game-shop to generate revenues. Product dif- ferentiation is one possibility to optimize the profitability of the game. In this paper, we use a microeconomic approach in order to highlight the implications of product differentiation for the profit maximization problem.
Keywords: 330; Fortnite; gaming; Freemium; product di erentiation; market segmentation